Comparison of matrix metalloproteinase levels in periodontal pockets treated with chlorhexidine and propolis - Ali Batuhan Bayırlı; Fulden Cantaş Türkiş; Ercan Saruhan; İbrahim Kıvrak (International Journal of Secondary Metabolite)
Natural antimicrobial products are attracting interest in the treatment of periodontal diseases due to their minimal or nonexistent side effects. Propolis, a complex resin content produced by bees, has drawn particular interest for its antibacterial effects, including inhibitory effects on periodontopathogenic bacterial species. This study compared the effects of propolis, a natural product, and chlorhexidine, the gold standard antimicrobial agent, on MMP-1 and MMP-9 levels in gingival crevicular fluid (GCF). Subgingival irrigations of chlorhexidine and propolis solutions were performed in selected deep periodontal pockets of periodontitis patients along with scaling and root planing. The treatment protocol was administered three times at one-month intervals starting from the initial day of the study. GCF MMP-1 and MMP-9 levels, along with clinical periodontal parameters, were evaluated before and after treatment. The study results showed that a statistically significant decrease in clinical periodontal parameters in both groups (p<0.001). Biochemical analysis revealed a statistically significant decrease in levels of GCF MMP-1 and MMP-9 in both groups (p<0.005). Additionally, the decrease in GCF MMP-1 levels was found to be significantly greater in the propolis group compared to the chlorhexidine group (p<0.001).